Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Iphone (Studi Kasus Mahasiswa Fisip Undip) - Galih Widiatmoko; Sudharto P Hadi (Jurnal Ilmu Administrasi Bisnis, 2016)
The increase in Rupiah exchange rate against the Dollar during the last 5 years go up significantly, but sales of Apple's smartphone experience fluctuations in the beginning down from 2012 to 2013, but again took place from 2013 to 2015. The purpose of this research is to know the influences between the variable pricing and varaiabel brand image against a decision of purchase Iphone on student and political science undip Semarang. The type of research used was explanatory research and sample used amounted to 100 students who purchase the Iphone product. The sampling technique used was purposive sampling and accidental sampling. The result of the discussion note that price and brand image influences the purchasing decisions as evidenced by regression analysis calculation of 0.727. While the brand image variables affect the brand image of 0.500 against purchasing decisions. However the variable brand image is more dominated by the results of a multiple regression test with 0.524 while the variable rates only 0.184.